Cross border Enforcement of Monetary Claims - Interplay of Brussels I A Regulation and National Rules: National Report: The Sweden - Linton, Marie (2018)
The "National Report: The Sweden" systematically and comprehensively addresses the main features of the enforcement of monetary claims in the German legal system, focusing in particular on the analysis of legal remedies in the enforcement procedure.   Said issues are approached from both national and cross-border perspectives. The issues discussed are  profoundlytopical in light of the recent coming into effect of the Brussels IA Regulation (Recast) and its more or less successful implementation in the national systems of the Member States, which has raised a number of issues. The report critically reflects some of the controversial solutions covered by the Recast Regulation regarding the effectiveness and appropriateness of the Regulation’s application in the legal system in question and related problems. It also deals with national specificities in the enforcement procedure, which still constitute an obstacle to cross-border procedures. The report was created as part of a study conducted under the auspices of the EU project BIARE ("Remedies on the Enforcement of Foreign Judgments according to Brussels I Recast") under the coordination of the Faculty of Law  University of Maribor.
Keywords: Brussels IA Regulation; cross-border enforcement procedure; enforcement of monetary receivables; legal remedies; Sweden